2014
DOI: 10.1002/clen.201300670
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Risk Evaluation of Tea Industry Coal Ash for Environmental Suitability

Abstract: Overload of coal ash (CA) generated from several coal fired plants poses acute problems of disposal and contamination of soil and water resources. Since CA generated from tea factories has not yet been characterized from environmental viewpoints, we attempted to critically characterize the agro-ecological compatibility of CA samples (CA1, CA2, CA3, and CA4) collected from four distantly located tea factories. Among these samples, we found CA3 and CA4 to have low pH and high metal content. Accordingly, we restr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
1
4
0
1
Order By: Relevance
“…The unburned carbon content was also measured with the loss on ignition (LOI), for which 22.81%, 16.65%, and 30.62% were obtained (see Table 1) for CFC 1, CFC 2, and CFC 3 respectively. Similar results have been reported by other authors (27,29), which is attributed to proportions of unburned coal; where the latter has been reported with high levels of PHA (13). Concerning toxicity, it has been found that one of the most frequent occupational risks is the risk of contracting cancer due to exposure to byproducts of coal combustion, due to the content of PHA and radioactive natural radionuclides, either by ingestion or dermal contact (4,37).…”
Section: Chemical and Elemental Compositionsupporting
confidence: 87%
See 2 more Smart Citations
“…The unburned carbon content was also measured with the loss on ignition (LOI), for which 22.81%, 16.65%, and 30.62% were obtained (see Table 1) for CFC 1, CFC 2, and CFC 3 respectively. Similar results have been reported by other authors (27,29), which is attributed to proportions of unburned coal; where the latter has been reported with high levels of PHA (13). Concerning toxicity, it has been found that one of the most frequent occupational risks is the risk of contracting cancer due to exposure to byproducts of coal combustion, due to the content of PHA and radioactive natural radionuclides, either by ingestion or dermal contact (4,37).…”
Section: Chemical and Elemental Compositionsupporting
confidence: 87%
“…In this sense, CFCs are characterized by being granular with an irregular hexagon structure and visibly porous (13, 26 -28). The morphology of unburned carbon in CFC appears as irregular shapes for the same technique (29). Silva & Da Boit (19) studied CFCs using SEM and found concentrations of ultrafine spherical particles and nanoparticles smaller than 50 nm, rich in silica crystals and predominance of fine quartz grains; where exposure to these crystals is related to the incidence of lung cancer.…”
Section: Morphology Of Cfcsmentioning
confidence: 99%
See 1 more Smart Citation
“…We determined water-soluble concentration of different elements in the MSW samples following Bhattacharyya et al (2011) and Goswami et al (2014). The samples were mixed with distilled deionized water (1:10 (w/v)) in conical flasks.…”
Section: Solubility Study and Geochemical Model (Visual Minteq)mentioning
confidence: 99%
“…Bununla birlikte, atık kül bileşenleri, toprak ve su kaynaklarını büyük ölçüde kirleten hem çözünür hem de çözünmeyen ağır metaller içermektedir [7]. Ayrıca uzun vadeli tarımsal uygulamalarda kullanımının toprak sağlığını etkileyebileceği ancak insan sağlığı risk analizi sonuçlarına göre ise, tüm çay fabrikası atık küllerinin metal konsantrasyonlarının, potansiyel kanser risk seviyelerinin altında olduğu belirtilmiştir [8].…”
Section: Introductionunclassified